Words at work and play three decades in family and community life - Heath, Shirley Brice (Cambridge University Press, 2012)
"Childhood and family life have changed significantly in recent decades. What is the nature of these changes? How have they affected the use of time, space, work and play? In what ways have they influenced face-to-face talk and the uses of technology within families and communities? Eminent anthropologist Shirley Brice Heath sets out to find answers to these and similar questions, tracking the lives of 300 black and white working-class families as they reshaped their lives in new locations, occupations and interpersonal alignments over a period of thirty years. From the 1981 recession through the economic instabilities and technological developments of the opening decade of the twenty-first century, Shirley Brice Heath shows how families constantly rearrange their patterns of work, language, play and learning in response to economic pressures. This outstanding study is a must-read for anyone interested in family life, language development and social change"-Publisher.